Technical Communication: Complex Nominals Used to Express new Concepts in Scientific English - Causes and Ambiguity in Meaning - Montero, Begoña (The ESPecialist, 2012)
The comprehension problems that multiword lexical units may give rise to is a common experience shared not only by readers of technical writings but also by lexicographers, lexicologists, terminologists and technical translators. An examination of the reader´s difficulties in comprehension may reveal that certain linguistic and discourse features are more liable to misunderstandings. Nominal compounds are a usual way of expressing new concepts in scientific English despite the problems of ambiguity they may convey. For this purpose, a survey has been conducted from a corpus of these structures extracted from technical texts, i.e. instruction manuals and technical reports or specifications of devices, textbooks, or general or specialized journals.